Use of Aspects of Constructivism in Shaping Ecological Awareness - Buchcic, Elżbieta (Studia Ecologiae et Bioethicae, 2021)
Nowadays, the pedagogical aspects of shaping ecological awareness in society are a very important topic in the context of negative changes taking place in the natural environment, and the constantly growing anthropo-pressure. However, it is a very broad issue that needs to be considered in many ways, from the point of view of many scientific fields, including pedagogy, psychology, sociology, and philosophy, based on the natural sciences. It is always worth considering as a priority, the formal and informal education of the whole society, and not only children and adolescents, because it is adults who manage the environment. It should also be remembered that knowledge is not only facts, principles, and theories, derived from the observation of phenomena and events, but also the ability to rationally use and interpret this information in everyday life. Therefore, using the assumptions of constructivist pedagogy, it is possible to enrich the offer of activities aimed at shaping the ecological awareness of the entire society. The article presents selected assumptions of constructivist pedagogy, and the possibility of implementing it, while shaping correct attitudes towards nature. It is constantly worth looking for an answer to the question of how to shape ecological awareness, in order to gradually reduce people's attitude to “have” and increase the attitude of “to be”. The appreciation of the value of nature is also essential for the realisation of the idea of sustainable development, which is the only hope for a “better tomorrow”. Currently, a specific determinant of environmental protection are specific activities related to the broadly understood relationship of man - culture - nature. However, the interdependencies are conditioned by factors of cultural influence on the environment, and the influence of the environment on the preferred values.